British Dietetic Association's Obesity Specialist Group dietetic obesity management interventions in children and young people: review & clinical application. Issue 1 (10th November 2020) - Stewart, L.; Easter, S.
Abstract: Background: Dietitians play a vital role in the management of childhood obesity. To support that role the Obesity Specialist Group of the British Dietetic Association commissioned a review and clinical application paper. This current paper is a summary of that review document, which is available on the BDA's website. Methods: The initial sources of evidence were guidelines, published reviews and government guidance. Best practice advice was sought from networks including the BDA's Obesity and Paediatric Specialists groups. The original document was reviewed by a review group and members of the Obesity and Paediatric Specialist group's committees. Results: The overall aim of dietetic interventions in childhood weight management should be to deliver evidence based dietetic weight management care, which helps maintain positive lifestyle changes. To support this aim the review recommends the UK BMI cut off points in setting service referral and triaging criteria. Ensuring the whole child's world is taken into account when undertaking assessment and throughout the programme process is essential. Dietitians working in this field require behavioural change skills, motivational techniques and the ability to communicate to children of differing ages and their parents. Knowledge of local child safe guarding procedures are necessary for all working in this field. Recommendations on basic and advanced skills required are specified. Conclusions: This paper was written to compliment a full review document. The complexities around case management, child protection issues and competing family motivations require dietitians trained at undergraduate and postgraduate level to deliver high quality weight management and behavioural change. Abstract : Graphic abstract outlining the main messages for the dietetic management of childhood obesity.